2019
DOI: 10.1136/bmjophth-2018-000248
|View full text |Cite|
|
Sign up to set email alerts
|

Metagenomics in ophthalmology: current findings and future prospectives

Abstract: Less than 1% of all microorganisms of the available environmental microbiota can be cultured with the currently available techniques. Metagenomics is a new methodology of high-throughput DNA sequencing, able to provide taxonomic and functional profiles of microbial communities without the necessity to culture microbes in the laboratory. Metagenomics opens to a ‘hypothesis-free’ approach, giving important details for future research and treatment of ocular diseases in ophthalmology, such as ocular infection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 92 publications
0
51
0
1
Order By: Relevance
“…The large fall out of articles was partly due to a high yield of research on the flower iris (publications n = 549) and publications on veterinarian topics (publications n = 859). Based on the inclusion criteria, 76 articles were included: 35 reported on original research (27 on human ocular surface amplicon sequencing, 5 on murine ocular surface amplicon sequencing (Terzulli et al 2015; de Paiva et al 2016; Kugadas et al 2016; St. Leger et al 2017; Wan et al 2018), 1 on intra‐ocular amplicon sequencing and 2 publications using shotgun sequencing), 14 reviews (Willcox 2013; Zegans & Van Gelder 2014; Kugadas & Gadjeva 2016; Lu & Liu 2016; Boost et al 2017; St. Leger & Caspi 2018; Wen et al 2018; Baim et al 2019; Borroni et al 2019; Gallon et al 2019; Watane et al 2019; Cavuoto et al, 2019a, 2019b, 2019c; Ozkan & Willcox 2019) and 27 abstracts (summarized in Table ). When taking into account only amplicon sequencing research on human ocular surface, there is an evident increase in original publications since 2016 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The large fall out of articles was partly due to a high yield of research on the flower iris (publications n = 549) and publications on veterinarian topics (publications n = 859). Based on the inclusion criteria, 76 articles were included: 35 reported on original research (27 on human ocular surface amplicon sequencing, 5 on murine ocular surface amplicon sequencing (Terzulli et al 2015; de Paiva et al 2016; Kugadas et al 2016; St. Leger et al 2017; Wan et al 2018), 1 on intra‐ocular amplicon sequencing and 2 publications using shotgun sequencing), 14 reviews (Willcox 2013; Zegans & Van Gelder 2014; Kugadas & Gadjeva 2016; Lu & Liu 2016; Boost et al 2017; St. Leger & Caspi 2018; Wen et al 2018; Baim et al 2019; Borroni et al 2019; Gallon et al 2019; Watane et al 2019; Cavuoto et al, 2019a, 2019b, 2019c; Ozkan & Willcox 2019) and 27 abstracts (summarized in Table ). When taking into account only amplicon sequencing research on human ocular surface, there is an evident increase in original publications since 2016 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These studies showed dysbiotic changes in the mycobiomes under diseased conditions and also revealed that certain fungal species exist at low levels without causing disease but may become pathogenic under immune-compromised conditions [ 36 ]. Compared to the above human niches that have been sampled for fungi, studies on the eye are rare [ 37 , 38 ] and even more rare are studies analysing the mycobiome of the vitreous fluid of the eye [ 1 , 11 , 39 ]. Further, detection of fungi in intraocular fluids secondary to systemic infection is extremely rare and the causative agents are often difficult to cultivate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, finding the causative pathogen often presents a problem with traditional ocular surface microbiological culture methods. It is estimated that the causative pathogen is correctly identified in only 4 in 10 cases of ocular infection with classical microbiological methods [ 46 ]. New approaches to the method of collecting corneal samples include the polytetrafluoroethylene (PTFE) impression membrane, which was found to have significantly better isolation rates compared to a surgical blade and was also less invasive [ 47 ].…”
Section: Risk Factors Clinical Presentation and Diagnosismentioning
confidence: 99%
“…New approaches to the method of collecting corneal samples include the polytetrafluoroethylene (PTFE) impression membrane, which was found to have significantly better isolation rates compared to a surgical blade and was also less invasive [ 47 ]. The evolution of metagenomic next-generation sequencing may provide an effective diagnostic aid to finding the pathogen responsible for causing keratitis, and may better help us understand the differences in the ocular surface microbiome between healthy individuals and patients with keratitis or predisposing risk factors, such as ocular surface disease [ 46 ]. Metagenomic shotgun sequencing has also revolutionised the taxonomic profiling of microorganisms present in the corneal graft preservation medium, which is another source of infection that can predispose one to keratitis post-procedure, especially since topical corticosteroids are used to prevent graft rejection [ 48 ].…”
Section: Risk Factors Clinical Presentation and Diagnosismentioning
confidence: 99%